(untitled) (European Journal of Teaching and Education, 2023)
Entrepreneurship education at universities tends to neglect entrepreneurial soft skills such as uncertainty competence and resilience. Art-based teaching and learning are considered as an effective way of fostering such competencies but have hardly been described in the context of entrepreneurship education. This paper explores what and how students learn from integrating a studio approach into entrepreneurship education. The research object is a teaching event on developing a business idea through painting. The two-day workshop encompassed instructions by an artist, students painting on large-size canvases, and an extended crit. The case study was informed by teaching conversations, student statements, lecturers’ observations, and resulting field notes. The data reveal that the creative process made participants reflect on the entrepreneurial mindset. Students experienced self-efficacy and learned how to embrace uncertainty. Although the qualitative approach of this study lacks generalizability, the case adds to research and practice by underpinning the potential of art-based entrepreneurship education in fostering entrepreneurial competence.